P72 Feasibility of combined structural and functional proton lung imaging in young children with cystic fibrosis. (11th November 2022) - Yule, A; Ng, C; Palaniyappan, N; Peggs, Z; Bradley, C; Brooke, J; Deelschaft, N; Spiller, R; Hoad, C; Francis, S; Gowland, P; Hall, I; et al.
Abstract : Introduction: Cystic Fibrosis Transmembrane Regulator (CFTR) modulator therapies target multiple organ systems, but chiefly improve lung health. Modulators have maximal benefit when commenced in early childhood. There is a need for sensitive assessment of lung health in children. We have developed an MRI protocol to assess lung structure and function, as part of a multi-organ multimodal MRI CF study in young children. Herein we present the lung imaging feasibility data. Aims: To demonstrate the feasibility of this protocol in children 6–11 years. Methods: Children aged 6 – 11 years with CF, or healthy controls were recruited in a modified version of the GIFT-CF3 protocol (NCT04618185 ). A fasting gut and liver MRI was followed by a set meal, a gut and lung scan at 240 min immediately followed by a further meal then a gut scan at 300 min. Lung sequences included free-breathing lung Ultra Short Echo (UTE) and free breathing Phase Resolved Functional Lung (PREFUL). No breath holds are required for these scans. Other sequences included small bowel water content, colon volumes and gut motility, MR liver elastography (MRE), fat, and derived portal pressure. Children were distracted by watching a film during the scanning. Results: 17 children (14 CF, 3 controls) were recruited and undertook a scanning day prior to the commencement of elexacaftor-tezacaftor-ivacaftor (ETI). Mean age was 9.0 years (range 6.0 to 11.9). Lung sequences were obtained in 16/17 children. 16/17 children completed the scanning protocol despite a whole day of multiple scans and the young age of the participants. Representative images are shown ( figure 1 ). Conclusion: We have collected baseline pulmonary MRI structural and functional data on 14 children with CF and 3 controls. We plan to collect data on matched controls and further follow up imaging of children with CF after commencing ETI. Please refer to page A214 for declarations of interest related to this abstract.